Analysis of The Role of Psychology in Education at SMP Negeri 5 Pamona Puselemba - Tarukallo*, Yohanis; Novince, Atika; Tudjuka, Masril Aguswandi; Erliana, Ni Made; Sigilipu, Fries Pileman Soa'e; Tobondo, Yuyun Alfasius (Universitas Syiah Kuala, 2023)
Education is the learning of knowledge, skills, and habits of a group of people passed down from one generation to the next through teaching, research, and training. Psychology is a scientific discipline that examines human behavior and human mental processes and studies the influence of the mental state of organisms and the external environment of individuals. The purpose of this study was to analyze the role of psychology in learning at SMP Negeri 5 Pamona Puselemba. The role of the teacher or educator is very important in knowing the psychology of children. Teachers need to continuously try to understand those they will lead in the educational process; teachers need to study the basic characteristics of students. At SMPN 5 Pamona Puselemba, several psychological factors influence students' education, namely family factors, environmental conditions, intelligence, and interests and talents.